A study on the cracking behaviour in laser metal deposition of IC10 directionally solidified nickel-based superalloy. (December 2015) - Xing, B.; Chang, B. H.; Yang, S.; Du, D.
Abstract : IC10 superalloy has been applied in manufacturing aircraft engine components, and the repair of damaged components is required because of high costs involved in replacement. In this work, the cracking behaviour and cracking sensitivity were investigated during laser metal deposition on IC10 superalloy. The results indicate that cracks with diverse morphology mainly appear at the interface between deposition layer and the substrate; in rapid heating period of laser metal deposition, the liquid phase rich of low-melting point γ ′– γ eutectic compositions will occur at the grain boundaries of IC10 superalloy. In the following rapid solidification process, the residual liquid phase will form the liquid film, which can be broken easily under tensile stress, and finally form cracks at deposit/substrate interface. Moreover, when the heat input increases, the number of cracks will increase while the average length of cracks does not change so significantly.